Targeting mPGES-2 to protect against acute kidney injury via inhibition of ferroptosis dependent on p53 - Zhong, Dandan; Quan, Lingling; Hao, Chang; Chen, Jingshuo; Qiao, Ranran; Lin, Tengfei; Ying, Changjiang; Sun, Dong; Jia, Zhanjun; Sun, Ying (Cell death & disease, 2023)
Acute kidney injury (AKI) is a clinical syndrome with high morbidity and mortality but no specific therapy. Microsomal prostaglandin E synthase-2 (mPGES-2) is a PGE 2 synthase but can metabolize PGH 2 to malondialdehyde by forming a complex with heme. However, the role and mechanism of action of mPGES-2 in AKI remain unclear. To examine the role of mPGES-2, both global and tubule-specific mPGES-2-deficient mice were treated with cisplatin to induce AKI. mPGES-2 knockdown or overexpressing HK-2 cells were exposed to cisplatin to cause acute renal tubular cell injury. The mPGES-2 inhibitor SZ0232 was used to test the translational potential of targeting mPGES-2 in treating AKI. Additionally, mice were subjected to unilateral renal ischemia/reperfusion to further validate the effect of mPGES-2 on AKI. Interestingly, both genetic and pharmacological blockage of mPGES-2 led to decreased renal dysfunction and morphological damage induced by cisplatin and unilateral renal ischemia/reperfusion. Mechanistic exploration indicated that mPGES-2 deficiency inhibited ferroptosis via the heme-dependent regulation of the p53/SLC7A11/GPX4 axis. The present study indicates that mPGES-2 blockage may be a promising therapeutic strategy for AKI.